Evaluating Competitiveness in the Supply Chain Management of Small and Medium Scale Enterprises - Chaiyawit Muangmee; Nuttapon Kassakorn; Bilal Khalid; Radovan Bačík; Sebastian Kot (Journal of Competitiveness, 2022)
This research investigated Supply Chain Management (SCM) in Small and Medium Enterprises (SMEs) in Thailand, Slovakia, and Poland and compared the SCM practices among the three countries. The sole purpose was to first determine the various factors that influence SCM operations and SCM practices in each of the countries and then find out whether there is a difference among the three countries in terms of SCM operations and practices. The study was conducted using primary data collected from SME management personnel from the three countries. A structured questionnaire was used to collect the data using a 5-point Likert scale. The data was analyzed using multi-group Structural Equation Modeling (SEM). The results of the study indicated that supply chain management practices and operations adopted by the small and medium enterprises in Thailand, Slovakia, and Poland were invariant. The environmental sustainability elements in SCM and the social aspects of sustainability in SCM have positively influenced SCM practices in all countries. The study recommended that SMEs in the countries should consider adopting the factors that support SCM, operationalizing the SCM through enhancing the capabilities of the end-user, and vitally taking into consideration the environmental sustainability elements in SCM, such as environmentally-friendly production processes, taking action towards waste management, and adopting production processes that inhibit the emission of harmful substances into the atmosphere by encouraging the implementation of policies that foster the use of renewable energy sources in production.
Keywords: Sustainable Supply Chain Management